1989
DOI: 10.2307/1131079
|View full text |Cite
|
Sign up to set email alerts
|

Learned Helplessness, Test Anxiety, and Academic Achievement: A Longitudinal Analysis

Abstract: The stability of individual differences in test anxiety and learned helplessness over a 2-year period and their relation to concurrent and future school achievement were examined. Several issues regarding the assessment of learned helplessness are also addressed. 82 children were administered measures of test anxiety and helplessness in the third grade and again in the fifth grade. Teachers also provided reports of learned helpless and mastery-oriented behaviors at these 2 grade levels. It was found that: (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 0 publications
1
74
0
2
Order By: Relevance
“…This finding shows consistency with other results published in current relevant literature (e.g., Chapell et al, 2005;Culler & Holahan, 1980;Fincham, Hokoda, & Sanders, 1989;Seipp, 1991). Other studies have found that learning and academic achievement decrease as a result of high anxiety, and increase as a result of reinforcement and anxiety free learning atmospheres (Hembree, 1988;Rana & Mahmood, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding shows consistency with other results published in current relevant literature (e.g., Chapell et al, 2005;Culler & Holahan, 1980;Fincham, Hokoda, & Sanders, 1989;Seipp, 1991). Other studies have found that learning and academic achievement decrease as a result of high anxiety, and increase as a result of reinforcement and anxiety free learning atmospheres (Hembree, 1988;Rana & Mahmood, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the use of quantitative methods to approach this research question would complete such qualitative explorations. Also, despite there are a few studies examining the relationship between academic achievement and test anxiety levels of students (e.g., Carden, Bryant, & Moss, 2004;Chapell, Blanding, Silverstein, Takahashi, Newman, Gubi, & McCann, 2005;Culler & Holahan, 1980;Fincham, Hokoda, & Sanders, 1989), the relationship between teaching-learning conceptions and academic achievement with the mediating role of test anxiety in this context is not present in the relevant literature. While teachers' teaching-learning conceptions might have an impact on the academic achievement levels of students, test anxiety may have a significant role in the relationship between those two variables.…”
Section: Introductionmentioning
confidence: 99%
“…Development of the SBC is consistent with Gronlund's (1971) criteria for improving scale construction as the attributes being rated are directly observable as behaviours, categories and points in the scale are defined clearly, between three and seven rating positions are provided, and the characteristics being rated are recognised as being of educational significance. However, Fincham et al (1989) reported that although the learned helpless and mastery orientation subscales are highly correlated (r = -0.81), the psychometric robustness of the checklist had not been established. Further, the issue of whether the SBC specifically measured learned helplessness and mastery orientation or whether the items reflected academic competence (Harter, 1983) had not been addressed.…”
Section: Measurement Of Learned Helplessnessmentioning
confidence: 99%
“…The SBC, presented in Appendix 1, is composed of 24 items, with 12 items designated by Fincham et al (1989) as measuring learned helplessness (items 1, 4, 6, 8, 9, 12, 14, 17, 18, 20, 21, 23) and 12 items as measuring mastery orientation (items 2, 3, 5, 7, 10, 11, 13, 15, 16, 19, 22, 24). The extent to which the learned helpless and mastery-oriented items describe students' behaviour in the classroom over the previous two to three months is rated by their teacher on a five-point Likert scale ranging from 1 (not true) through 3 (somewhat or sometimes true) to 5 (very true).…”
Section: Student Behavior Checklistmentioning
confidence: 99%
See 1 more Smart Citation